evaluation of academic management in virtual learning environments (Revista Electrónica REDINE, 2019)
Research on the evaluation of academic management in virtual learning environments was framed in the positivist paradigm under the quantitative approach, as well as based on an evaluative design of a descriptive nature, aimed at evaluating academic management in virtual environments. apprenticeship of the Law School of the Deanship of Legal and Political Sciences of the Fermín Toro University, with headquarters in Raúl Quero Silva Building in El Ujano, Iribarren municipality of Lara State, the target population consisted of 67 facilitators, 3 Chief SAIA and 1 School Director, for a total of 69 participants. In order to collect the information, a Likert-type questionnaire was structured, which was validated using the expert judgment technique and its reliability using the Cronbach's Alpha coefficient, resulting in 0.79, considered highly reliable. The results coincided with the researcher's premise when generating guidelines in order to improve educational processes and the strengthening of professional competences of Law students at Fermín Toro University.